Inventory of molecular markers affecting biological characteristics of avian influenza A viruses - Suttie, Annika; Deng, Yi-Mo; Greenhill, Andrew R.; Dussart, Philippe; Horwood, Paul F.; Karlsson, Erik A. (Virus genes, 2019)
Avian influenza viruses (AIVs) circulate globally, spilling over into domestic poultry and causing zoonotic infections in humans. Fortunately, AIVs are not yet capable of causing sustained human-to-human infection; however, AIVs are still a high risk as future pandemic strains, especially if they acquire further mutations that facilitate human infection and/or increase pathogenesis. Molecular characterization of sequencing data for known genetic markers associated with AIV adaptation, transmission, and antiviral resistance allows for fast, efficient assessment of AIV risk. Here we summarize and update the current knowledge on experimentally verified molecular markers involved in AIV pathogenicity, receptor binding, replicative capacity, and transmission in both poultry and mammals with a broad focus to include data available on other AIV subtypes outside of A/H5N1 and A/H7N9.